Sectarian and Secular: Lay Perspectives in Stūpa Burials at Mount Zhongnan During the Tang Dynasty (AD 618–906) - Wen Sun (Religions)
The canonical limitations on stūpa burial for ordinary monks and prohibitions on non-Buddhist stūpas underwent significant changes in medieval China. A key question emerges when considering how the use of stūpas expanded beyond honoring the Buddha and saints to include lay individuals. People’s interpretation of stūpas—whether they were clergy or lay followers—varied based on their distinct social contexts, living circumstances, and religious beliefs. This article examines lay participation in the stūpa forest at Mount Zhongnan in Chang’an during the seventh and eighth centuries, drawing primarily on inscriptions evidence. By reassessing funerary stūpas erected for laypeople at Mount Zhongnan, this article calls for a reconsideration of the traditional sectarian view of lay-oriented funeral rituals. Even within the laity, motivations for constructing funerary stūpas differed. For some lay Buddhists, the Three Stages teachings influenced their burial practices, while for others without a direct connection to this community, stūpa burials were often more personal, centered on family commemoration. This study highlights the interplay between religious rituals and social structures, as evidenced by the historical and cultural significance of specific material culture.